Investigation of the mechanical response of laminated composites reinforced with different type wire mesh - Alev, Kubranur Isgor; Kaman, Mete Onur; Albayrak, Mustafa; Yanen, Cenk (Springer Heidelberg, 2023)
In this study, the mechanical behavior of laminated glass fiber composite plates reinforced with wire meshes under in-plane and out-of-plane loads was investigated. For this purpose, composite plates were produced by vacuum infusion method by placing aluminum and glass fiber wire layers with different mesh numbers between woven glass fiber fabrics. Afterward, impact and tensile tests were applied to the obtained specimens, respectively. The effect of the added reinforcement wires meshes on the impact resistance and tensile strength of the composites was determined. According to the data obtained; When glass wire with the same mesh number is used, 19.2% more reaction force was obtained than aluminum wire. The results of the double cantilever beam (DCB) and end notched flexure (ENF) test results confirmed that glass wire meshes had a better adhesion surface compared to aluminum. In addition, critical energy release rates were obtained with the help of the ANSYS & REG; finite element program and the data were compared with the experimental results. In the case of increasing the mesh number, it was observed that the reaction force of the glass wire mesh reinforced composite decreased by 17.54% under the impact. It was determined by scanning electron microscope (SEM) images that this decrease in the reaction force occurred due to the matrix material contacting the interlayer adhesion surfaces to a lesser extent. One layer of wire mesh reinforcement had no significant effect on the tensile strength of the glass fiber composite.
Keywords: Glass fiber composite; Delamination; Wire mesh; Energy release rate; Impact